2021
DOI: 10.1037/dhe0000174
|View full text |Cite
|
Sign up to set email alerts
|

Epistemic exclusion: Scholar(ly) devaluation that marginalizes faculty of color.

Abstract: Faculty of color experience a number of challenges within academia, including tokenism, marginalization, racial microaggressions, and a disconnect between their racial/ethnic culture and the culture within academia. The present study examined epistemic exclusion as another challenge in which formal institutional systems of evaluation combine with individual biases toward faculty of color to devalue their scholarship and deem them illegitimate as scholars. Using data from interviews with 118 faculty of color fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
198
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(200 citation statements)
references
References 87 publications
1
198
0
1
Order By: Relevance
“…Together, bias toward marginalized scholars and bias toward intersectionality lead to critiques of the work as self‐serving and self‐motivated, which negatively affects intersectionality scholars’ careers, particularly those scholars from marginalized groups. Consistent with other research on epistemic exclusion generally, the epistemic exclusion of intersectionality scholars may reduce their sense of belonging in the field, result in less positive evaluations of their work (because intersectionality scholarship is placed in lower impact journals), or create pressure for them to reject intersectionality in favor of dominant theoretical and empirical approaches (Settles, Jones, Buchanan, & Dotson, 2020a; Settles, Jones, Buchanan & Brassel, 2020b).…”
Section: The Epistemic Exclusion Of Intersectionality Is a Barrier Tosupporting
confidence: 62%
See 1 more Smart Citation
“…Together, bias toward marginalized scholars and bias toward intersectionality lead to critiques of the work as self‐serving and self‐motivated, which negatively affects intersectionality scholars’ careers, particularly those scholars from marginalized groups. Consistent with other research on epistemic exclusion generally, the epistemic exclusion of intersectionality scholars may reduce their sense of belonging in the field, result in less positive evaluations of their work (because intersectionality scholarship is placed in lower impact journals), or create pressure for them to reject intersectionality in favor of dominant theoretical and empirical approaches (Settles, Jones, Buchanan, & Dotson, 2020a; Settles, Jones, Buchanan & Brassel, 2020b).…”
Section: The Epistemic Exclusion Of Intersectionality Is a Barrier Tosupporting
confidence: 62%
“…Empirical work supports that epistemic exclusion operates through both formal and informal processes (Settles, Buchanan, & Dotson, 2019; Settles, Jones, Buchanan, & Dotson, 2020a). In their interviews with faculty of color, Settles, Jones, Buchanan and Dotson (2020a) found that participants felt their scholarship was formally devalued in systems of evaluation (e.g., annual review, promotion, and tenure) when their work focused on marginalized groups, used methods outside of the disciplinary center (e.g., qualitative methods), or focused on addressing social problems. Evaluation metrics, such as journal impact factors and grant funding (Hoppe et al., 2019; Roberts, Bareket‐Shavit, Dollins, Goldie, & Mortenson, 2020), codified these assumptions and subsequently contributed to evaluation inequities (e.g., Gruber, 2014; Settles, Jones, Buchanan, & Dotson, 2020a).…”
Section: Epistemic Exclusion Theorymentioning
confidence: 99%
“…Some of these social forces work against the scholarship of UR scientists being valued and taken into account, so that proactive efforts are required to anticipate and counteract their ability to relegate the contributions of UR scientists to the margins. Institutional norms of assessment and individual biases continuously reinforce environments that devalue the scholarship and legitimacy of faculty and scholars of color, a concept known as epistemic exclusion (Settles et al, 2020). In a recent study, epistemic exclusion was reported to have been experienced in the workplace by 55% of UR participants (Settles et al, 2019).…”
Section: Recognize That Epistemic Exclusion Exists In Sciencementioning
confidence: 99%
“…Preferred training modalities and topics may differ for traditionally underrepresented researchers who often face specific barriers in pursuing prevention research and funding (Franco et al 2011;Waitzkin et al 2006). For example, previous research has identified barriers such as greater university service responsibilities, having less access to research facilities, and having limited mentorship availability by researchers of color (Alegria et al 2019;Hemming et al 2019;Hoppe et al 2019;Settles et al 2020). These barriers, among others, can negatively impact the research career trajectory and perpetuate limited representation of people of color in prevention research (Lee et al 2012).…”
Section: Growth and Change In The Needs Of Prevention Scientistsmentioning
confidence: 99%
“…This endorsement of training may be an accurate reflection of the support researchers of color feel they need given the barriers they face in pursuing prevention research and funding (Franco et al 2011;Waitzkin et al 2006). Additional training support may be especially needed given the limited representation of people of color in prevention research (Lee et al 2012), and other barriers found in prior research such as greater university service responsibilities, less access to appropriate research facilities, and few mentors of color (Alegria et al 2019;Hemming et al 2019;Hoppe et al 2019;Settles et al 2020).…”
Section: Strong Interest In Trainingmentioning
confidence: 99%